Cmapanalysis: an extensible concept map analysis tool - Alberto J. Cañas; Larry Bunch; Joseph D. Novak; Priit Reiska (Universidad de Granada, 2013)
Concept maps are used extensively as an assessment tool, and the literature is abundant with studies on the use of concept maps for assessment and on the assessment of concept maps. The assessment of concept maps can be an arduous process, in particular when assessing a large number of maps. CmapAnalysis is a software tool that facilitates performing various analysis measures on a collection of concept maps. A set of measures that consider size, quality and structure properties of the maps are included. The program is designed to be extensible, allowing users to add their own measures. The program is not intended to replace the individual evaluation of concept maps by teachers and instructors, as it does not capable of "understanding" the content of the maps. It is aimed at researchers who are looking for more general trends and measures across a large number of maps, and who can extend it with their own measures. The output of CmapAnalysis is an Excel spreadsheet that can be further analyzed.